2022
DOI: 10.3390/biom12020278
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Systemic Microvascular Dysfunction in Heart Failure with Preserved Ejection Fraction

Abstract: Heart failure with preserved ejection fraction (HFpEF) is a condition with increasing incidence, leading to a health care problem of epidemic proportions for which no curative treatments exist. Consequently, an urge exists to better understand the pathophysiology of HFpEF. Accumulating evidence suggests a key pathophysiological role for coronary microvascular dysfunction (MVD), with an underlying mechanism of low-grade pro-inflammatory state caused by systemic comorbidities. The systemic entity of comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 208 publications
1
9
0
2
Order By: Relevance
“…Moreover, a decrease in coronary microvascular function, an increased prevalence in coronary rarefaction, and an impaired maximal hyperemia, compared to age-matched controls, were also reported in HFpEF patients ( 25 28 ). For a more comprehensive review on this subject, see Weerts et al, ( 29 ).…”
Section: Vascular Contribution To Hfpefmentioning
confidence: 99%
“…Moreover, a decrease in coronary microvascular function, an increased prevalence in coronary rarefaction, and an impaired maximal hyperemia, compared to age-matched controls, were also reported in HFpEF patients ( 25 28 ). For a more comprehensive review on this subject, see Weerts et al, ( 29 ).…”
Section: Vascular Contribution To Hfpefmentioning
confidence: 99%
“…По этой причине механизмы и пути развития КМД становятся объектом изучения конкретных фармакологических мишеней, таких как оксид азота, саркомерный титин, трансформирующий фактор роста β, цитокины или аденозиновые рецепторы, воздействие на которые могло бы предотвратить развитие и прогрессирование эндотелиальной дисфункции, лежащей в основе развития данного состояния [4][5][6][7]. Тем не менее, остаются открытыми многие вопросы, а полученные новые данные по-прежнему не могут быть использованы для оптимизации терапевтических стратегий лечения, и необходимо дальнейшее изучение этой непростой, с экспоненциально растущим интересом к ней, проблемы [8].…”
Section: актуальностьunclassified
“…Это, с одной стороны, ухудшает физиологию эндотелия и периваскулярной среды, запуская сложные молекулярные пути, которые в конечном итоге приводят к развитию периваскулярного фиброза, повышенной миокардиальной жёсткости и снижению CFR [7]. С другой стороны, данные патофизиологические механизмы опосредуют прогрессирование гипоксии в тканях, что локально инициирует высвобождение воспалительных цитокинов, которые, в свою очередь, способствуют формированию интерстициального фиброза, тем самым запуская патологический круг микроциркуляторных изменений в миокарде [8,9].…”
Section: материал и методы исследованияunclassified
“…Even if the arterial AH is one of the most frequent causes of HFpEF, it is not clear if it is similar to those observed in hypertensive patients, such as the changes in micro-and macro-vascular structure which could be observed in HFpEF patients. Recent studies separately showed that HFpEF is associated with detrimental changes in retinal microcirculation and carotid arteries [15][16][17][18]. However, to our knowledge, no previous study has simultaneously evaluated retinal, carotid and left ventricle remodeling in patients with HFpEF.…”
Section: Introductionmentioning
confidence: 98%